KONSTRUKSI CINTA ILAHI JALALUDDIN RUMI - Nafiudin, Muhammad Aviv (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2024)
Jalaluddin Rumi was a Sufi and Muslim poet who contributed to the meaning of divine love. Interestingly, Rumi prefers poetry as a medium of expression of the depth of his divine love rather than theoretical concepts. It has not only inspired many scholars, both East and West, but Rumi's poetry has even received significant attention and recognition among the public. However, this in turn has negative consequences in the form of attempts among Western audiences to erase Rumi's Muslim identity. Therefore, this paper will discuss Rumi's construction of divine love with a philosophical review of how divine love becomes possible in a person as an answer to the disruptive efforts of Western audiences above. This research is a type of literature research that uses a descriptive-analytical method with an epistemological approach. This study found that the heart as an instrument and inner transformation as a process to bring a person to the stage of divine love in the construction of Rumi's thought is closely related to Islamic values themselves. Thus, the metaphorical representations in Rumi's teachings of love cannot be separated from the overall construction of divine love.